Solitary splenic metastasis from lung adenocarcinoma: A case report. Issue 5 (21st July 2017) - Hara, Kantaro; Izumi, Nobuhiro; Tsukioka, Takuma; Komatsu, Hiroaki; Toda, Michihito; Miyamoto, Hikaru; Suzuki, Satoshi; Kimura, Takuya; Shibata, Toshihiko; Nishiyama, Noritoshi
Abstract : Solitary splenic metastasis is extremely rare, with only 27 reported cases in the literature. An 81‐year‐old woman was referred to our hospital for treatment of pulmonary and splenic lesions. Chest computed tomography showed a small lung nodule in the right upper lobe, abdominal computed tomography showed an 8 cm splenic mass with abnormal accumulation, and positron emission tomography revealed a maximum standardized uptake value of 7.9. She had elevated serum cancer antigen 19‐9 (1847 U/mL) and carcinoembryonic antigen concentrations (17.9 ng/mL). She underwent laparoscopic splenectomy. Pathological examination revealed poorly differentiated adenocarcinoma. We performed partial lung resection and diagnosed the small lung lesion as lung adenocarcinoma. Both lesions were positive for thyroid transcription factor 1. Thus, primary lung adenocarcinoma and solitary splenic metastasis were diagnosed. The patient was still alive without recurrence four years postoperatively. Herein, we report a rare case of lung adenocarcinoma with solitary splenic metastasis and review the literature.